A Problem-Oriented Group Approach to Reduce Children's Fears and Concerns About the Secondary School Transition. Issue 1 (1st February 2018) - Vassilopoulos, Stephanos P.; Diakogiorgi, Kleopatra; Brouzos, Andreas; Moberly, Nicholas J.; Chasioti, Maria
Abstract : To facilitate students' transition into secondary school, a short, problem-oriented group program was designed that included interpretation retraining, problem solving, and social-skills training. Pre- and post-test data from two groups conducted over the course of 5 weeks were combined for a total of 35 6th-grade students waiting to undergo school transition. There was also a no-intervention control group ( n = 19). Results indicate that completion of the program by the intervention group led to a significant decrease on negative interpretations, with greater reductions in feelings of loneliness and increases in children's positive attitudes toward school compared to the control group. In addition, 3 months before moving to secondary school, children in the intervention group reported significantly fewer concerns about school transition compared with the controls. We conclude that the inclusion of problem-based strategies may be beneficial when designing transition groups, which may also lead to a significant reduction in worries and concerns about the transition to secondary school.